Students as non-standard employees: Exploring work related issues in students' perceptions on their term-time job - Ingo Winkler (Management Revue, 2008)
The article presents the results of an explorative study that aimed at exploring work related issues in students' perceptions of their job as atypical employees. An individual picture of the experienced work reality of students is drawn according to work task, flexible working hours, instructions and training opportunities, students' relations to other employees, and social integration. By adopting a qualitative design, I was able to emphasize the subjective perspective of students describing their very own experiences as flexible workers. The study revealed various perceptions of students working as flexible employees and related this picture to current empirical and theoretical research in the field of non-standard employment.
Keywords: 650; Term-time employment; students'work experiences; non-standard employment; flexible employment